Determination of International Logistics Policy on GCSM Performance and World Class SME Capabilities: The Indonesian Case - Al Farizi, Muhammad (Journal of World Trade Studies, 2023)
Business globalization encourages Indonesian SMEs to accelerate their business to enter the global market to raise Indonesia's creative economy. Logistics governance is crucial because penetrating the international market requires a standardized logistics system and high environmental policy compliance. So this study aims to analyze the sustainable supply chain capabilities of SMEs in improving the capabilities of Indonesian SMEs towards world-class, focusing on four of the 13 dimensions: international logistics, traditional logistics, provision, and inventory. The survey-based quantitative approach was chosen to target SME owners in Indonesia with purposive sampling withdrawal. The data results from 113 respondents who participated by filling out an online questionnaire were analyzed using the Structural Equation Modelling-Partial Least Square (SEM-PLS) analysis technique. The results showed that traditional logistics significantly affected MSME inventories and logistics internationalization. Good inventory management affects the ability of SMEs to supply goods or services. International logistics has an impact on the efficiency of supply chain management. It has the potential to increase global market access. Green Supply Chain Management (GSCM) is also important, affecting the efficiency of sustainable supply chains and the ability of SMEs in world business. GSCM efficiency can optimize resources, reduce environmental impact, and increase the competitiveness of SMEs in the global market. By implementing GSCM, SMEs can be innovative and strong in global competition.